Zachowania prozdrowotne licealistów na tle wybranych miast - Gumola, Katarzyna (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
The subject of health behaviors are high school students. The aim of the study was to compare the results of different centers in the aspect of self-health, cognition, attitudes, behaviors and health habits of respondents. Based on the analysis of documents (results of studies by different authors) are indicated on the topics necessary for the continuing implementation of teaching young people at every level of education. The habits of a healthy lifestyle from an early age must be implemented and ongoing environmental example shown and communicated. The test results show that the test secondary school students in the most are familiar with determinants of health, in particular their negative impact on human health. Only 52% of respondents care about health, taking up physical activity, regular feeding, caring for personal hygiene and adequate amount of sleep. The test results of different provinces are similar, dominates the tendency of decreasing activity with age of the youth.